PENGARUH TERPAAN TAYANGAN SINETRON 'IKATAN CINTA' TERHADAP SIKAP EMPATI PENONTON TELEVISI (Survei pada Komunitas Fanbase Ikatan Cinta dalam Grup Chat Telegram Ikatan Cinta RCTI) - Misqadya Aqila Hariesda, (2022)
Ikatan Cinta is one of the most popular Indonesian soap operas during the Covid-19 pandemic. The success of the soap opera Ikatan Cinta in conveying messages to the audience created various reactions from the audience. The crowds of viewers in responding to this soap opera make 'Ikatan Cinta' has its own phenomenon. This study focuses on how much influence the exposure to the soap opera Ikatan Cinta has on the empathetic attitude of television viewers. The survey method used by researchers to distribute questionnaires to 99 respondents who are members of the Group Chat Ikatan Cinta RCTI on Telegram. Researcher also used cultivation theory which is usually used to measure the attitude of the audience and its relation to the effects of television. In analyzing data, the researcher conducted validity and reliability tests, correlation tests, simple linear regression tests, coefficient of determination, and hypothesis testing. The frequency indicator on the concept of exposure is the most influential on the empathy attitude of television viewers. The results showed that there was a strong relationship between exposure to the soap opera Ikatan Cinta and the attitude of empathy for television viewers with a correlation value of 0.613. The coefficient of determination shows that the influence of exposure to the soap opera Ikatan Cinta on the empathy attitude of television viewers is 37.6% and the rest is influenced by other factors. This result is strengthened by the results of hypothesis testing which states that H0 is rejected and H1 is accepted, which means that there is a significant effect on exposure to the soap opera Ikatan Cinta on the empathetic attitude of television viewers. Researchers hope that further research can find out more about other factors that can affect viewers due to watching television.